Mathematical model and solution approaches for integrated lot-sizing, scheduling and cutting stock problems - Melega, Gislaine Mara; Araujo, Silvio Alexandre de [UNESP]; Morabito, Reinaldo (Springer, 2020)
In this paper, we address a two-stage integrated lot-sizing, scheduling and cutting stock problem with sequence-dependent setup times and setup costs. In production stage one, a cutting machine is used to cut large objects into smaller pieces, in which cutting patterns are generated and used to cut the pieces, and should be sequenced in order to obtain a complete cutting plan for the problem. The cut pieces, from production stage one, are used to assemble final products in production stage two, where the final products are scheduled in order to meet the client's demands. To solve the two-stage integrated problem, we present solution methods based on a price-and-branch approach, in which a column generation procedure is proposed to generate columns and the integer problem is solved by decomposition solution approaches. A computational study is conducted using randomly generated data and an analysis showing the impact of the solution approaches in the two-stage integrated problem is presented. In addition, the performance and benefits of the integrated approach are compared to an empirical simulation of the common practice (sequential approach).
Keywords: Cutting stock and scheduling problems; Lot-sizing and scheduling problems; Sequence-dependent setups; Price-and-branch approaches